2020
DOI: 10.1021/acs.iecr.0c04037
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids-Promoted Electrocatalytic Reduction of Carbon Dioxide

Abstract: The excessive consumption of global fossil fuels leads to the rapid increase of CO2 content in the atmosphere, causing serious consequences, such as global warming, which have attracted extensive attention from the international community. As a kind of abundant and inexpensive carbon resource, CO2 can be converted into high-utilization chemicals and fuels, and its resource utilization is of great significance to environmental protection and energy security. Among the many CO2 conversion technologies, electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 162 publications
0
34
0
Order By: Relevance
“…Bohlen et al [46] performed the electrodeposition of indium from 1:2 M choline based DES (ChCl:EG-1:2), employed them as an electrocatalyst for the electrochemical reduction of CO 2 to formate. As per the Cui et al [15] review, this was the first publication which reported on the preparation of CO 2 reduction catalysts by electrodeposition in DESs. Extending this method by tailoring the DES electrolyte properties and the electrodeposition conditions, it is possible to develop other metals with different sizes, shapes and structures and faces.…”
Section: Co 2 Electroreduction In Deep Eutectic Solvents (Dess)mentioning
confidence: 93%
See 2 more Smart Citations
“…Bohlen et al [46] performed the electrodeposition of indium from 1:2 M choline based DES (ChCl:EG-1:2), employed them as an electrocatalyst for the electrochemical reduction of CO 2 to formate. As per the Cui et al [15] review, this was the first publication which reported on the preparation of CO 2 reduction catalysts by electrodeposition in DESs. Extending this method by tailoring the DES electrolyte properties and the electrodeposition conditions, it is possible to develop other metals with different sizes, shapes and structures and faces.…”
Section: Co 2 Electroreduction In Deep Eutectic Solvents (Dess)mentioning
confidence: 93%
“…Ionic liquids have recently attracted a lot of interest as electrolytes because of their high CO 2 adsorption capacity, solubility, selectivity to CO 2 over other gases (such as N 2 , O 2 , CH 4 ), and low energy consumption. They are a very diverse and efficient family of promoters in the electrochemical reduction of CO 2 , with the ability to improve reaction characteristics by changing their interaction and exhibiting high electrochemically stable windows (4-5 V), high ionic conductivities, and low vapour pressures [10,15]. Also, it has been observed that ILs can lower the energy barrier of reactions by building complexes with the intermediates generated during the reaction [28].…”
Section: Co 2 Electroreduction In Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrolyte is the medium for electrochemical reduction of CO 2 , which also has a great influence on the interactions among the electrocatalysts, CO 2 and its intermediates [1f,8] . Compared with aqueous electrolytes (e. g., 0.5 M KHCO 3 ), [9] ionic liquid (IL) has higher CO 2 capture ability, stronger ionic conductivity, and wider potential windows, which is considered as a promising electrolyte for CO 2 electroreduction [1d,10] . The special microenvironment of IL is conducive to dissolving and activating CO 2 molecules, and reducing the reaction energy barrier of CO 2 anion radicals’ formation [1d,10c] .…”
Section: Figurementioning
confidence: 99%
“…Compared with aqueous electrolytes (e. g., 0.5 M KHCO 3 ), [9] ionic liquid (IL) has higher CO 2 capture ability, stronger ionic conductivity, and wider potential windows, which is considered as a promising electrolyte for CO 2 electroreduction [1d,10] . The special microenvironment of IL is conducive to dissolving and activating CO 2 molecules, and reducing the reaction energy barrier of CO 2 anion radicals’ formation [1d,10c] . Meanwhile, it also can coordinate with the catalysts to regulate the catalytic performance of CO 2 electroreduction [11]…”
Section: Figurementioning
confidence: 99%